Hurricane lizards and plastic squid : the fraught and fascinating biology of climate change - Hanson, Thor (Basic Books, 2021)
"In his three previous books-Feathers, The Triumph of Seeds, and Buzz-Thor Hanson has taken his readers on unforgettable journeys into nature, rendered with great storytelling, the soul of a poet, and the insight of a biologist. In this new book, he is doing it again, but exploring one of the most vital scientific and cultural issues of our time: climate change. As a young biologist, Hanson by his own admission watched with some detachment as our warming planet presented plants and animals with an ultimatum: change or face extinction. But his detachment turned to both concern and awe, as he observed the remarkable narratives of change playing out in each plant and animal he studied. In Hurricane Lizards and Plastic Squid, Hanson tells the story of how nature-both plants and animals, from beech trees to beetles-are meeting the challenges of rapid climate change head-on, adjusting, adapting, and sometimes noticeably evolving. Brown pelicans are fleeing uphill, seeking out new lives in the mountains. Gorillas in Uganda are turning to new food sources, such as eucalyptus trees (which humans only imported to Africa in the past several decades), as their old sources wain. Auklets, a little sea bird, aren't so lucky: changes in the lifecycles of their primary food source means they return at specific times of year to oceanic feeding grounds expecting plankton blooms that are no longer there. As global warming transforms and restructures the ecosystems in which these animals and others live, Hanson argues, we are forced to conclude that climate change will not have just one effect: Some transformations are beneficial. Others, and perhaps most, are devastating, wiping out entire species. One thing is constant: with each change an organism undergoes, the delicate balance of interdependent ecosystems is tipped, forcing the evolution of thousands more species, including us. To understand how, collectively, these changes are shaping the natural world and the future of life, Hanson looks back through deep time, examining fossil records, pollen, and even the tooth enamel of giant wombats and mummified owl pellets. Together, these records of our past tell the story of ancient climate change, shedding light on the challenges faced by today's species, the ways they will respond, and how these strategies will determine the fate of ecosystems around the globe. Ultimately, the story of nature's response to climate change is both fraught and fascinating, a story of both disaster and resilience, and, sometimes, hope. Lyrical and thought-provoking, Hurricane Lizards and Plastic Squid is poised to transform the conversation around climate change, shifting the focus from humans to the lattice of life, of which humans are just a single point"--